1981
DOI: 10.1029/rs016i006p01047
|View full text |Cite
|
Sign up to set email alerts
|

The importance of coherence in inverse problems in optics

Abstract: A summary of current inverse problems of statistical optics is presented together with a short guide to the pertinent review-type literature. The retrieval of structural information from the far-zone degree of coherence and the (time-averaged) intensity distribution of radiation scattered by a superposition of random and periodic scatterers is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Previous theoretical work [1][2][3][4] suggested that interferometry may in fact permit the detection of source periodicity which might otherwise be indiscernible because the radiated intensity is too diffuse . In particular, it was predicted [4] that the resulting far-zone .…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical work [1][2][3][4] suggested that interferometry may in fact permit the detection of source periodicity which might otherwise be indiscernible because the radiated intensity is too diffuse . In particular, it was predicted [4] that the resulting far-zone .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on the phase retrieval problem have already been performed (see, for example, Ferwerda 1978, Saxton 1978, Ross eta1 1980. Studies ofthe phase retrieval using the numerical procedure have been actively conducted in recent years (see for example, Gerchberg and Saxton 1972, Fienup 1978, 1979, 1982, Walker 1982, Fright and Bates 1982, Bates and Fright 1983, Chalasinska-Macukow and Arsenault 1985.…”
Section: Introductionmentioning
confidence: 99%